ANALISIS KESADARAN BIOPHILIA PADA SIVITAS AKADEMIKA FAKULTAS DESAIN UNIVERSITAS KOMPUTER INDONESIA - Dina Fatimah; Lia Warlina; Salsabila Zahra Multifah (Narada : Jurnal Desain dan Seni, 2023)
By incorporating nature, both physically and in its natural forms, into the design, biophilic design gives people the chance to live and work in a healthy environment and lead prosperous lives. This study uses the Faculty of Design at the Indonesian Computer University as a case study. The goal of this study is to examine user awareness tools for the Biophilia idea and seek for chances to apply it more precisely. The user's understanding of the idea of biophilia is gauged using the quantitative descriptive technique. This study's findings indicate that the UNIKOM Faculty of Design's academic community has a strong awareness of biophilia. If anything goes above and beyond expectations, it might be a future assessment of how educational facilities are used to improve teaching and learning that is tied to the physical and psychological needs of its users.